Science Practicum Activities through Freshwater Bioremediation Experiments on Biotechnology Materials in Junior High Schools - Fathurrohman, Irfan; Prima, Eka Cahya; Riandi, Riandi (Jurnal Pendidikan MIPA, 2023)
This research aims to design practical learning for bioremediation of aquatic ecosystems from dye waste by utilizing enzymes extracted from baglog waste. The topic chosen was bioremediation of water polluted by acid blue 113. Purpose of this practicum is to provide in learning science by conducting a practicum that supports environmental sustainability. Variables in this study were enzyme extracts taken from baglog waste of brown oyster mushroom and the percentage of textile dyedecolorization. As a results showed that the percentage of decolorization of wastewater polluted by acid blue dye 113 was as follows: concentrations of 30 ppm (45.41%), 45 ppm (49.7%), 60 ppm (35.08%), and 75 ppm (23.09%). The enzyme extract of mushroom baglog waste can effectively degrade the content of acid blue 113 textile dye which is dissolved in water. This study is the first to be conducted in Indonesia which can be done easly and using available materials. Keywords: bioremediation, decolorization, baglog waste, mushroom.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp264-274